Perancangan Sistem Informasi Penjualan Sepatu Pada Toko Lacobucci Berbasis Web - Luthfia Putri Nabilla; Agung Perdananto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
In this era, information technology is an integral part of our lives. In almost every sector in any area have all used information technology. The same is true of sales information systems that business leaders have widely used for time efficiency. The purpose of the system's existence is to solve some of the problems at lacobucci's which is the data archiving that still manually so that gives an increased risk for human error and of course takes a lot of time because it has to create a report by manually checking the sales data one by one. The system is web based and uses the waterfall method. A convenient method for software development with unchanging specifications. As for the software used in the manufacture of this system is mysql as the data storage and the programming language used is PHP and javascript. It is hoped that this new sales information system will make it easier to sales transactions data processing and be able to solve existing problems.